W.E.B. Du Bois’s Constructivist Theory of Justice - Basevich, Elvira (Journal of moral philosophy, 2022)
This essay presents the normative foundation of W.E.B. Du Bois’s constructivist theory of justice in three steps. First, I show that for Du Bois the public sphere in Anglo-European modern states consists of a dialectical interplay between reasonable persons and illiberal rogues. Second, under these nonideal circumstances, the democratic ideal of autonomy grounds reasonable persons’ deliberative openness, an attitude of public moral regard for others which is necessary to construct the terms of political rule. Though deliberative openness is the essential vehicle of construction, reasonable persons only have a pragmatic political obligation to forge ties of deliberative reciprocity with likeminded persons whom they trust will listen and not harm them. Finally, I present Du Bois’s defense of black suffragists’ support of the 19th Amendment to illustrate pragmatic political obligation in action. I sketch successful democratic engagement that reconstitutes a nonideal public sphere.